2017
DOI: 10.1080/09638288.2017.1315183
|View full text |Cite
|
Sign up to set email alerts
|

The social trajectory of brain tumor: a qualitative metasynthesis

Abstract: Multiple changes typically occur across the social trajectory of brain tumor, including a loss of pre-illness networks and the emergence of new ones. Understanding the barriers and facilitators for maintaining social connection may guide interventions for strengthening social networks and enhancing well-being in the context of brain tumor. Implications for rehabilitation Social networks and roles are disrupted throughout the entire trajectory of living with brain tumor Physical, cognitive and psychological fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 61 publications
1
46
0
1
Order By: Relevance
“…Therefore, it may be beneficial for clinicians to assess perceptions of functional impairment and the subsequent impact on participation in social activities and roles. Previous research identified that people may avoid social interaction due to self‐consciousness about physical and cognitive symptoms . It is recommended that psychological interventions focus on supporting people to maintain connection with valued SGMs through use of compensatory strategies and modified activity participation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, it may be beneficial for clinicians to assess perceptions of functional impairment and the subsequent impact on participation in social activities and roles. Previous research identified that people may avoid social interaction due to self‐consciousness about physical and cognitive symptoms . It is recommended that psychological interventions focus on supporting people to maintain connection with valued SGMs through use of compensatory strategies and modified activity participation.…”
Section: Resultsmentioning
confidence: 99%
“…Further, as well as having positive functions, social groups can produce rather than alleviate stress during major life transitions . A qualitative metasynthesis of brain tumor research found that the perceived helpfulness of SGMs varied. Although many appreciated support provided by their SGMs, others reported an overabundance of support that evoked feelings of dependency .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations